The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species - Mound, Laurence A.; Wang, Jun; Tree, Desley J. (Zootaxa, 2020)
A key to 19 species from Australia in the genus Hoplothrips is provided, including 11 described as new species: H. bellingeni, H. giganteus, H. lamingtoni, H. lihongae, H. lowdeni, H. nelsoni, H. oakeyi, H. reedi, H. tarsus, H. woodsi, H. wrightae. One species, H. semicaecus (Uzel), is recorded in Australia for the first time, and H. corticis (De Geer) and H. orientalis (Ananthakrishnan) are newly recorded from the Australian mainland. Structural diversity among the species of the genus Hoplothrips is discussed. Members of this genus share many character states with species of Deplorothrips, Hoplandrothrips and Psalidothrips that also live as fungal-hyphal feeders on dead branches and in leaf litter.